1992
DOI: 10.1093/ajh/5.11.787
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Culturally Influenced Lay Models of Hypertension to Compliance With Treatment

Abstract: Problems in compliance with treatment and illness management have frequently been traced to differences between patients' explanatory models of illness and the biomedical model. We investigated the relationship of cultural beliefs about hypertension to compliance with treatment. Using semistructured interviews, we elicited the explanatory models of hypertension held by 60 black hypertensive women being treated at Charity Hospital in New Orleans. The patient sample was followed for 2 months to obtain data on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 0 publications
12
70
0
2
Order By: Relevance
“…Also consistent with other studies, the patients in this study viewed stress as an important causal factor. 7,8,[26][27][28][29] This suggests that stress is a fundamental and cross-culturally embedded dimension in a patient's EM of hypertension. Our results also suggest, however, that this EM may be more common among hypertensive immigrant patients than it is among indigenous populations and that migration is often seen as a trigger for stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also consistent with other studies, the patients in this study viewed stress as an important causal factor. 7,8,[26][27][28][29] This suggests that stress is a fundamental and cross-culturally embedded dimension in a patient's EM of hypertension. Our results also suggest, however, that this EM may be more common among hypertensive immigrant patients than it is among indigenous populations and that migration is often seen as a trigger for stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, patient adherence to hypertension treatment is often poor, particularly among ethnic minority populations in Western Europe and the USA. 1,[6][7][8] According to the theoretical model of medical anthropologist Kleinman, healthcare providers and patients have different 'explanatory models' (EMs) of sickness and treatment, including explanations for the aetiology of the condition, the timing and onset of symptoms, the patho-physiological processes involved, the natural course and severity, and appropriate treatments. 9,10 Lay EMs vary according to personality and socio-cultural factors, whereas those of healthcare providers rely more on scientific logic and evidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of familiarity contributed to ''vague[ness] about illness management... and they did not understand that they had a role in managing their illness beyond taking medication.'' In addition to lack of exposure to biomedical care, culturally varying health beliefs may also influence patients' health-seeking behaviors and willingness to comply with treatment regimens [22,77]. For example, in a study of prophylactic TB treatment among Vietnamese immigrants, researchers found recent immigrants were more reluctant to complete the medication regimen because its side effects were deemed too ''hot'', ''while Asian herbal medicines were [seen as] more benign and cooling'' [57, p. 352].…”
Section: Health Literacy and Patient Adherencementioning
confidence: 99%
“…One study of black women found that the word hypertension had morphed into the term high-pertension, that is, perceptions that their tension in fact was high. 14 We surmise that lay people hear the word hypertension and interpret it to mean: hyper-too much and tension-stress. Studies of conceptualizations or explanatory models of hypertension have found as many as 50% of patients endorsing stress as a significant cause of hypertension.…”
Section: Language Of Hypertension 453mentioning
confidence: 99%